Analyzing Visual Signals as Visual Scenes. Issue 7 (25th February 2013) - ALLEN, WILLIAM L.; HIGHAM, JAMES P.; Higham, James P.; Semple, Stuart
Abstract The study of visual signal design is gaining momentum as techniques for studying signals become more sophisticated and more freely available. In this paper we discuss methods for analyzing the color and form of visual signals, for integrating signal components into visual scenes, and for producing visual signal stimuli for use in psychophysical experiments. Our recommended methods aim to be rigorous, detailed, quantitative, objective, and where possible based on the perceptual representation of the intended signal receiver(s). As methods for analyzing signal color and luminance have been outlined in previous publications we focus on analyzing form information by discussing how statistical shape analysis (SSA) methods can be used to analyze signal shape, and spatial filtering to analyze repetitive patterns. We also suggest the use of vector‐based approaches for integrating multiple signal components. In our opinion elliptical Fourier analysis (EFA) is the most promising technique for shape quantification but we await the results of empirical comparison of techniques and the development of new shape analysis methods based on the cognitive and perceptual representations of receivers. Our manuscript should serve as an introductory guide to those interested in measuring visual signals, and while our examples focus on primate signals, the methods are applicable to quantifying visual signals in most taxa. Am. J. Primatol. 75:664–682, 2013. © 2013 Wiley Periodicals, Inc.